2020
DOI: 10.1002/prop.202000010
|View full text |Cite
|
Sign up to set email alerts
|

Global Double Field Theory is Higher Kaluza‐Klein Theory

Abstract: Kaluza-Klein Theory states that a metric on the total space of a principal bundle P → M, if it is invariant under the principal action of P, naturally reduces to a metric together with a gauge field on the base manifold M. We propose a generalization of this Kaluza-Klein principle to higher principal bundles and higher gauge fields. For the particular case of the abelian gerbe of Kalb-Ramond field, this Higher Kaluza-Klein geometry provides a natural global formulation for Double Field Theory (DFT). In this fr… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
63
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 15 publications
(63 citation statements)
references
References 106 publications
0
63
0
Order By: Relevance
“…Notice that, in the particular case of a tensor hierarchy where all the fields do not depend on the internal space R2n, the curvature reduces to the familiar equations of a doubled torus bundle, i.e. truerightFleft=normaldscriptAleft0.28emΩcl2(U,double-struckR2n),rightHleft=normaldscriptB+12A,dAleft0.28emΩcl3(U),which is exactly the curvature of the String(Tn×Tn)‐bundle araising in the case of a globally geometric T‐duality, as explained in [1]. Also the gauge transformations reduce to truerightAI0.28emleft0.28emAI+normaldλI,rightscriptB0.28emleft0.28emscriptB+normaldnormalΞfalse⟨λ,scriptFfalse⟩.The local field FnormalΩnormalcl2false(U,R2nfalse) can thus be globalized to the curvature of a doubled torus bundle with 1st Chern class false[scriptFfalse]H2false(M,Z2nfalse).…”
Section: Review Of Proposals For Dft Geometrymentioning
confidence: 99%
See 1 more Smart Citation
“…Notice that, in the particular case of a tensor hierarchy where all the fields do not depend on the internal space R2n, the curvature reduces to the familiar equations of a doubled torus bundle, i.e. truerightFleft=normaldscriptAleft0.28emΩcl2(U,double-struckR2n),rightHleft=normaldscriptB+12A,dAleft0.28emΩcl3(U),which is exactly the curvature of the String(Tn×Tn)‐bundle araising in the case of a globally geometric T‐duality, as explained in [1]. Also the gauge transformations reduce to truerightAI0.28emleft0.28emAI+normaldλI,rightscriptB0.28emleft0.28emscriptB+normaldnormalΞfalse⟨λ,scriptFfalse⟩.The local field FnormalΩnormalcl2false(U,R2nfalse) can thus be globalized to the curvature of a doubled torus bundle with 1st Chern class false[scriptFfalse]H2false(M,Z2nfalse).…”
Section: Review Of Proposals For Dft Geometrymentioning
confidence: 99%
“…As argued in [6] and [3], DFT should be interpreted as a generalization of Kaluza‐Klein Theory where it is the Kalb‐Ramond field, and not a gauge field, that is unified with the pseudo‐Riemannian metric in a bigger space. Since the Kalb‐Ramond field is geometrized by a bundle gerbe, in [1] we proposed that DFT should be globally interpreted as a field theory on the total space of a bundle gerbe, just like ordinary Kaluza‐Klein Theory lives on the total space of a principal bundle. In the reference we showed how to derive some known doubled spaces such as the ones describing T‐folds, and how to interpret T‐duality.…”
Section: Introductionmentioning
confidence: 99%
“…We remark that, in this more general setting, the doubled space M is not required to be a product space. References [51] and [52] explore the idea that a general doubled space M is globally not a smooth manifold, but a more generalised geometric object (see there for details). In particular, in the references, it is derived that the patching conditions for local coordinate patches U (γα) = 0 is satisfied, we do not encounter problems for X * dx M = dX(σ) being periodic.…”
Section: Jhep06(2021)059mentioning
confidence: 99%
“…In particular, in the references, it is derived that the patching conditions for local coordinate patches U (γα) = 0 is satisfied, we do not encounter problems for X * dx M = dX(σ) being periodic. In other words, a doubled string can naturally live on a doubled space M that is patched in a more general way than a manifold (like the proposal by [51] and [52]) exactly because X(σ) does not appear in the action, but only X (σ) does.…”
Section: Jhep06(2021)059mentioning
confidence: 99%
“…An extension similar to (1.2) was considered in [FRS16], where symmetries of a gerbe with connection were investigated in relation with higher geometric prequantisation. Infinitesimal versions of the extension (1.2) were considered in [Col11,FRS16], where it was shown that these give rise to the standard H -twisted Courant algebroid on M, where H is the 3-form curvature of the connection on G. These considerations have been expanded on and applied to higher versions of Kaluza-Klein reductions of string theory in [Alf20].…”
Section: Introductionmentioning
confidence: 99%